Bidirectional chromosome replication in Bacillus subtilis 168. - Harford, N (1975)
Density transfer analysis of deoxyribonucleic acid from Bacillus subtilis 168 thy spores germinating in 5-bromouracil medium shows the order of replication of genetic markers to be: purA16, cysA14, sacA, ctrA, (narB, arol), dal, (hisA1, purB6), (tre-12, thr-5), (argA, aroG, argC4), (metC, leu-8, pheA), (ura-1, aroD), lys-1, (trpC, metB, ilvA, citB, citK, gltA). The precise order of transfer of markers within parentheses could not be determined in these experiments. Taken together with new PBS1 transduction data presented here and in the accompanying paper of J. Lepesant-Kejzlarová, J.-A. Lepesant, J. Walle, A. Billaut, and R. Dedonder (1975), the results can be resolved in terms of a symmetric, fully bidirectional mode of chromosome replication with a replication origin close to the purA16 marker and a terminus in the region of the gltA, citK loci, diametrically opposed to the origin. A new genetic map of the B. subtilis 168 chromosome is presented.